Pengaruh saving motives, pengalaman positif terhadap keputusan membeli asuransi dengan kecenderungan membeli sebagai variabel mediasi - Pratiwi Indah Nurhayati; Mellyza Silvi (Journal of Business & Banking, 2018)
The purpose of this study is to examine the influence of saving motives, positive experience on insurance purchasing decision with the inclination to purchase as mediation variable. The number of respondents from this study are 295 respondents. Respondents criteria in this study such as having insurance and being a decision maker to buy insurance and live in Surabaya, Gresik and Tuban. The technique to analyze the data use Partial Least Square Structural Equation Modeling (PLS-SEM) by using PLS 6.0 program. The results of this study explain that saving motives, and positive experience have a significant positive influence on insurance purchasing decision, while the inclination to purchase can mediate the influence of competency and positive experience on insurance purchasing decision.